2019
DOI: 10.1038/s41598-019-44854-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profile of NLRs and AIM2 in Glioma and Implications for NLRP12 in Glioblastoma

Abstract: Gliomas are the most prevalent primary brain tumors with immense clinical heterogeneity, poor prognosis and survival. The nucleotide-binding domain, and leucine-rich repeat containing receptors (NLRs) and absent-in-melanoma 2 (AIM2) are innate immune receptors crucial for initiation and progression of several cancers. There is a dearth of reports linking NLRs and AIM2 to glioma pathology. NLRs are expressed by cells of innate immunity, including monocytes, macrophages, dendritic cells, endothelial cells, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Reduced mRNA levels of NLRC4 are evident in the tumor tissues of colorectal cancer 118 . However, more recent studies have demonstrated normal levels in lung tumors 119 and hepatocellular carcinoma, 120 along with increased expression in breast cancer and glioma 121,122 . The role of NLRC4 in tumor regulation and suppression is not always consistent even in the same tumor model (Table 4), as discussed further below.…”
Section: Nlrc4 In Cancermentioning
confidence: 95%
“…Reduced mRNA levels of NLRC4 are evident in the tumor tissues of colorectal cancer 118 . However, more recent studies have demonstrated normal levels in lung tumors 119 and hepatocellular carcinoma, 120 along with increased expression in breast cancer and glioma 121,122 . The role of NLRC4 in tumor regulation and suppression is not always consistent even in the same tumor model (Table 4), as discussed further below.…”
Section: Nlrc4 In Cancermentioning
confidence: 95%
“…The Kaplan-Meier survival curves for CpGs that are significantly prognostic after adjusting for age, gender, tumor grade, and IDH1 mutation are presented in Figure 2(Ci-Civ) for DFS along with forest plot visualization of hazard ratios with 95% CI in Figure 2D. For cg07425555 (Figure 2Ci), the median DFS of high methylation ("Meth") versus low methylation ("Unmeth") was 72 (52-91) months versus 31 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) months (p < 0.001). For cg26969888, the median DFS of Meth versus Unmeth was 63 (44-83) months versus 30 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) months (p < 0.001).…”
Section: Association Between Podnl1 Aberrations and Tumor Aggressiveness In Lggmentioning
confidence: 99%
“…The role of NLRP12 in attenuating these inflammatory disorders was explained by the fact that NLRP12 downregulates NF-κB and ERK activation in T cells [71]. Deficiency of NLRP12 also promotes proliferation of osteocytes, hepatocytes, and microglia [28,76,77]. In the intestine, NLRP12-mediated regulation of inflammatory responses may shape gut microbiota composition [78,79].…”
Section: Nlrp12 and Inflammatory Disordersmentioning
confidence: 99%